The Effect of FDR, NPF and Liquidity Ratio on Profitability of Islamic Banks in Indonesia - Harjanti, Wulandari; Farhan, Ali (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This article discusses the phenomena of liquidity, non-performing loans and finance to deposit and their effect on profitability in Islamic banks. By using a sample of the financial statements of Mandiri Syariah, BRI Syariah, BNI Syariah, and Muammalat in the period January 2018 – December 2021 which were analyzed with multiple linear regression, it was concluded that NPL/NPF had a negative and significant effect on bank profitability, while Liquidity Ratio and FDR had an effect on positive and significant on bank profitability.